Pengaruh Tayangan Berita Kriminal terhadap Perilaku Kenakalan Remaja di Desa Senaung Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Suryadi; Ishak Abd. Aziz (Islamic Journalism Department/ Program Studi Jurnalistik Islam, 2022)
The author's research approach uses descriptive qualitative methods where the procedures used to produce data are generated from something that is written or spoken by people or through observable behavior. While collecting data the author uses research by conducting interviews, observation, and documentation. In analyzing the authors reduce data, display data, and draw conclusions. The results of this study show that criminal news shows really influence the delinquent behavior of teenagers in Senaung Village. However, this influence does not always have a negative impact and also does not always have a positive impact. The influence of criminal news shows on juvenile delinquency depends on the personality of the teenager. Are they able to control themselves in watching criminal news shows so that they fall prey to criminal acts.